MASUKNYA KEMBALI PERANCIS DALAM NORTH ATLANTIC TREATY ORGANIZATION (NATO) DI BAWAH KEPEMIMPINAN PRESIDEN NICOLAS SARKOZY - Sanjaya, Helmy Adi (Global and Policy Journal of International Relations, 2015)
ABSTRACTThis study discusses how idiosyncratic influence on the policies, which in this case is idiosyncratic to the 23rd French President Nicolas Sarkozy to the French re-entry into the North Atlantic Treaty Organization (NATO). The background of this study is to see how idiosyncratic Nicolas Sarkozy during life by using a social background psychobiography with Nicolas Sarkozy during childhood to become a French politician Nicolas Sarkozy affects the characteristics of leadership that became ambitious and ultimately influence policy decision making to select the French return again in the NATO defense pact.Keywords: Nicolas Sarkozy, Idiosyncratic, Psychobiography, Ambition, Decision Making, NATODOI:https://doi.org/10.33005/jgp.v3i01.1961